Cannibalistic behavior and functional response in Chrysomya albiceps (Diptera : Calliphoridae) - Faria, L. D.; Trinca, L. A.; Godoy, WAC (Kluwer Academic/plenum Publ, 2004)
Chrysomya albiceps is a facultative predator and cannibal species during the larval stage. Very little is known about cannibalism and prey size preference, especially in blowflies. The purpose of this investigation was to determine the influence of prey size and larval density on cannibalism by third-instar larvae of C. albiceps under laboratory conditions. Our results indicate that no cannibalism occurs by third-instar larvae on first- and second-instar larvae, but third-instar larvae do eat second-instar larvae. The functional response on second-instar larvae is consistent with Holling type II. The consequences of consuming second-, compared to first- or third-, instar larvae as well as the implications of cannibalism for the population dynamics of C. albiceps are discussed.
Keywords: cannibalism; prey development stage; foraging theory; functional response; Chrysomya albiceps; Calliphoridae